Investigating and Preventing Crime in the Digital Era New Safeguards, New Rights - Bachmaier Winter, Lorena; Ruggeri, Stefano (Cham : Springer International Publishing : Imprint: Springer, 2022)
The aim of this book is to delve into the impact of the Information and Communications Technologies in the criminal prevention and investigation, by addressing the state of the art of different measures and its implementation in different legal systems vis à vis the protection of human rights. Yet this research not only pursues a diagnostic goal but furthermore aims at providing a reconstruction of this problematic area in light of modern, human rights-oriented notion of criminal justice. This broadens the scope of this investigation, which encompasses both unprecedented safeguards to traditional, or anyway widely recognized individual rights and the emergence of new rights, such as the right to informational self-determination, and the right to information technology privacy. The book addresses the problems and potentials in the areas of criminal prevention and criminal investigation, taking into account that due to electronic surveillance and the progress in the use of big data for identifying risks, the borders between preventive and investigative e-measures is not clear-cut.
Preface: The Digital Revolution and Human Rights Challenges -- Part I - Crime Control and Criminal Inquiries in a Digitalised World. New Frontiers -- Criminal Investigation, Technological Development, and Digital Tools: Where are We Heading? -- Geolocation in Crime Detection and Prevention -- Big Data and Satellites: Between Safety of Airspace and Criminal Liability -- Facial Recognition for Preventive Purposes: The Human Rights Implications of Detecting Emotions in Public Spaces -- Part II - ICT Tools and New Investigative Techniques -- The Use of Drones and the New Procedural Safeguards in Crime Control and Criminal Investigation -- Search and Seizure of Digital Evidence: Human Rights Concerns and New Safeguards -- Digital Privacy and Cyber-Interception of Communications. A new scenario needs new concept -- Part III - Fact-Finding and Human Rights Challenges in the Digital Era -- AI-Powered Investigations: From Data Analysis to an Automated Approach toward Investigative Uncertainty -- Online Hearings and the Right to Effective Defence in Digitalised Trials -- The Digital Transition in Criminal Trials: New Promises, New Risks, New Challenges.
Keywords: Private international law; Conflict of laws; International law; Comparative law; Law-Europe.; Criminal law-International unification; Information technology-Law and legislation; Mass media-Law and legislation; Human rights; Criminal law; Private International Law, International and Foreign Law, Comparative Law; European Criminal Law; IT Law, Media Law, Intellectual Property; Human Rights; Criminal Law and Criminal Procedure Law